A Sequential Analysis of the Welfare Effects of Mobile Phones in Africa. (April 2019) - James, Jeffrey
The main purpose of this article is to assess the welfare effects of situations in which either mobile phone devices or SIM cards (or both) are not owned by relatively poor inhabitants of African countries. The task is pursued in a sequential analytical framework where effects at different stages of the process influence the welfare impact at later stages. Much of the analysis is conducted in different institutional circumstances from those found in the West (notably sharing and renting). Perhaps the main result of the analysis—backed by ample empirical evidence—is that the fewer are the alternatives to mobile phones as forms of communication (e.g., public transport), the greater tend to be the gains from this technology. In the particular case of leapfrogging, the fewer are fixed-line phones, the more do mobiles yield gains to poor users, whether these be individuals or actual countries. It is thus the context in addition to the technology that determines the differential welfare gains.